Textual and Personal Dialogues: Carmela Eulate Sanjurjo, Ana Roqué de Duprey and Puerto Rican Feminism at the Beginning of the 20th Century (Anclajes, 2017)
This article proposes that the novel Luz y sombra (1903) by Ana Roqué develops an intertextual dialogue with La muñeca (1895) by Carmela Eulate Sanjurjo. This dialogue recognizes both La muñeca’s artistic quality as well as its intent to transform the narrative in order to deliver a clearer moral message to its readers. While high levels of ambiguity and irony characterize Carmela Eulate’s novel—features which are responsible for a wide range of diverse and even contradictory interpretations—Ana Roque’s text develops a pedagogic discourse that avoids ambiguity. Her message emphasizes the importance of an education that allows women to choose a husband based on love and companionship instead of economic and social goals, so that marriage becomes the basis of a society capable of progressing.
Keywords: Carmela Eulate; Ana Roqué; La muñeca; Luz y sombra; Puerto Rico; 19th century